Islet-cell, thyroid, and gastric autoantibodies in diabetic identical twins. Issue 6009 (6th March 1976) - Lendrum, R; Nelson, P G; Pyke, D A; Walker, G; Gamble, D R
Abstract : Sera from 54 pairs of identical twins, 29 discordant and 25 concordant for insulin-dependent diabetes, and 11 pairs of concordant non-insulin dependent identical twins were examined for pancreatic islet-cell antibodies (ICAs). ICAs were found in 10 of the 29 diabetic discordant and eight of the 50 concordant twins (difference not significant P greater than 0-05). Six out of nine twins tested within one year of onset of diabetes were positive, whereas nine out of 29 tested after one to 10 years and three out of 41 tested after 10 years were positive. Only one of the 22 non-insulin-dependent twins had ICAs. Repeat ICA testing in five pair of insulin-dependent twins and in the siblings of one pair showed that ICAs may be present in people with normal glucose tolerance' may precede clinical diabetes by several years; and may decline in titre or disappear with increasing duration of disease. Thyroid or gastric autoantibodies, or both, were found in 36 out of 108 insulin-dependent twins and three out of 22 non-insulin dependent twins (difference not significant P less than 0-05). Only four twins had both ICAs and thyrogastric antibodies. There were no significant associations between autoantibodies and HLA histocompatibility types. As ICAs are more common in the diabetic than the non-diabetic twins of the discordant pairs they must be associated with juvenile onset diabetes. ICAs may appear some years before the onset of diabetes, but their prevalence declines with increasing duration of diabetes. The factors determining the production of ICA differ from those for thyroid and gastric autoantibodies.